2015
DOI: 10.1007/s00706-015-1414-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and analgesic effects of two new flavone C-glycosides from Panzeria alaschanica

Abstract: Two new flavone C-glycosides, named as panzeroside A and B were isolated from the n-BuOH crude extract of the aerial parts of Panzeria alaschanica Kuprian. Their structures were elucidated by spectroscopic methods, including UV, IR, ESI-MS, 1D NMR, and 2D NMR techniques. Anti-inflammatory and analgesic activities of were assessed in rats by the hot plate test, paw pressure, and carrageenan-induced paw oedema. The two new compounds showed significant and dose-dependent analgesic and anti-inflammatory effects. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Compound 227 had a higher anti-inflammatory potential than diclofenac (5 mg/kg b. w.), while the activity of compounds 139 and 140 were similar at 20-50 mg/kg b. w. doses. The butanol extract of this species furnished 2 other potentially anti-inflammatory compounds: the flavone C-glycosides panzeroside A (156) and B (157) [173]. A paw edema reduction volume in rats equal to that of 5 mg/kg b. w. of diclofenac was achieved with 30 mg/kg b. w. of both compounds.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 227 had a higher anti-inflammatory potential than diclofenac (5 mg/kg b. w.), while the activity of compounds 139 and 140 were similar at 20-50 mg/kg b. w. doses. The butanol extract of this species furnished 2 other potentially anti-inflammatory compounds: the flavone C-glycosides panzeroside A (156) and B (157) [173]. A paw edema reduction volume in rats equal to that of 5 mg/kg b. w. of diclofenac was achieved with 30 mg/kg b. w. of both compounds.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…B. lanata L.), 2 new flavone C-glycosides, named panzeroside A (156) and B (157), were isolated. The 2 new compounds demonstrated significant and dose-dependent analgesic and anti-inflammatory effects [173].…”
Section: Flavonoidsmentioning
confidence: 99%
“…However, there are few reported pharmacological studies [14] to support the therapeutic and medicinal effects of P. Alaschanica, and the mechanism of its beneficial effects has yet to be demonstrated. Previous phytochemical studies have revealed that P. alaschanica contains two new flavonoids, glycosides and phenylethanoids [15][16]. In this study, we investigated the effects of P. alaschanica as an anti-inflammatory candidate to inhibit paw edema formation in carrageenan-induced rat models of acute inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that P. lanata contains approximately 20 secondary metabolites including flavonoids, organic acids, and alkaloids [2–10]. Among them, flavonoids were the main bioactive components according to the recent studies such as the anti‐inflammatory and analgesic activities [11, 12].…”
Section: Introductionmentioning
confidence: 99%